Effects of roughness on the performance of axial flow cyclone separators using numerical simulation method. (November 2019) - Jun, Li; Ma, Chunyuan; Tao, Wang; Chang, Jingcai; Zhao, Xiqiang
An axial flow cyclone is a separator with high efficiency and low resistance. Researchers have extensively studied the structure and parameters that have the greatest influence on its performance. However, the influence of wall roughness on the performance of axial flow cyclones has been neglected for a long time. The wall roughness height can be changed by the manufacturing process and the effect of particles on the wall. Thus, in this study, the effects of roughness on an axial flow cyclone are investigated using a numerical simulation method. The Reynolds stress model and discrete phase model are used for gas and particle prediction and the simulation result were verified through experimentation. The results of the numerical simulation show that the roughness height has big influence on axial flow cyclones. The separation efficiency decreases and static pressure drop increases with increasing roughness height. This happens especially at high inlet velocity. The tangential velocity decreases, particularly near the inner surface of the cyclone, and axial velocity increases in the center of the pipe. The trends show that the degree of change reduced for all parameters with increasing roughness height.